Swahili in Academic Writing (Nordic Journal of African Studies, 2003)
Swahili, an important indigenous language of wider communication in Eastern and Central African countries, has been and continues to be used effectively in specialist communication for almost three decades now. It is widely used in the education domain particularly in Tanzania and Kenya. In Tanzania, the language is the sole medium of instruction in public primary schools and teachers' colleges training primary school teachers. It is also taught at high school and university levels. In Kenya, Swahili is a compulsory subject in primary and secondary schools and it is also offered in all public universities. The extensive use of the language in academia has led to the evolution of a special style of Swahili academic writing. The present paper is an attempt to bring to light the evolved linguistic features of the Swahili academic style. The paper looks at the orthographic, lexical, morphological and syntactic features of Swahili academic writing.